2022
DOI: 10.1101/gad.349284.121
|View full text |Cite
|
Sign up to set email alerts
|

A distinct core regulatory module enforces oncogene expression in KMT2A-rearranged leukemia

Abstract: Acute myeloid leukemia with KMT2A (MLL) rearrangements is characterized by specific patterns of gene expression and enhancer architecture, implying unique core transcriptional regulatory circuitry. Here, we identified the transcription factors MEF2D and IRF8 as selective transcriptional dependencies of KMT2A-rearranged AML, where MEF2D displays partially redundant functions with its paralog, MEF2C. Rapid transcription factor degradation followed by measurements of genome-wide transcription rates and superresol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 111 publications
2
21
0
Order By: Relevance
“…Thus, these findings can be complementary to our study and further explain the non-redundant function of MEF2D to IRF8. In line with Harada et al. (2022) highlighting the importance understanding the mechanism by which the IRF8/MEF2D TF circuit is activated, we found that AML carrying certain types of mutations, such as KMT2A -fusion and FLT3 ITD and NPM1c cooperating mutations ( Yun et al., 2021 ), can subsequently activate the MEF2D-IRF8 circuit and consequently require it for AML maintenance.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, these findings can be complementary to our study and further explain the non-redundant function of MEF2D to IRF8. In line with Harada et al. (2022) highlighting the importance understanding the mechanism by which the IRF8/MEF2D TF circuit is activated, we found that AML carrying certain types of mutations, such as KMT2A -fusion and FLT3 ITD and NPM1c cooperating mutations ( Yun et al., 2021 ), can subsequently activate the MEF2D-IRF8 circuit and consequently require it for AML maintenance.…”
Section: Discussionsupporting
confidence: 79%
“…Here, we leveraged comprehensive approaches to extensively demonstrate the essential role of MEF2D in AML, functionally characterized a patient-relevant intronic enhancer of MEF2D and uncovered the formation of the MEF2D-IRF8 circuit via binding to mutual enhancer element. To date, recent studies revealed the essential roles and activation of MEF2D in AML carrying KMT2A -r, and different mechanisms underlying AML maintenance by MEF2D were proposed, including inhibition of CEBPE-mediated myeloid differentiation program, and direct regulation of MYC and HOXA9, which is largely redundant with its homolog TF MEF2C ( Harada et al., 2022 ; Zhao et al., 2021 ). Although our model suggests the IRF8-MEF2D circuit and MYC program function in parallel in AML, we cannot entirely rule out the context- and cell type-specific roles of MEF2D.…”
Section: Discussionmentioning
confidence: 99%
“…MYB is a critical transcriptional dependency of acute myeloid leukemia (AML) 11,18,28,29 , where it has been a longterm focus of therapeutic efforts [30][31][32][33][34][35][36][37] , making AML a relevant context for functional characterization of MYB inhibitors. We therefore began by engineering a chemical degron model of MYB in AML cells.…”
Section: A Degron Model Reveals Direct Gene-regulatory Functions Of Mybmentioning
confidence: 99%
“…5 Recently, direct gene-regulatory functions of TFs have been established in pre-steady state assays where rapid TF degradation is coupled with measurements of genome-wide transcription rates. [8][9][10][11][12][13] These studies have demonstrated that TFs have narrow direct transcriptional programs and that long-term TF deprivation (e.g. after a CRISPR/Cas9-mediated knockout) leads to significant secondary effects obscuring a direct functional readout.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation